The Role of Entrepreneurial Finance in Fueling Growth and Innovation - Nurhayati, Nurhayati (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to explore the relationship between entrepreneurial finance and innovation, examining how various financing forms, such as venture capital, crowdfunding, and debt financing, influence the innovation process within companies. Additionally, the research investigates the impact of contextual factors like government regulations, market conditions, and entrepreneurial culture on the effectiveness of these financing mechanisms in promoting innovation. Research Design and Methodology: The study employs a systematic literature review to analyze existing research on entrepreneurial finance and innovation. By synthesizing findings from a wide range of sources, the research identifies key trends, challenges, and opportunities in the intersection of finance and innovation across different sectors and regions. Findings and Discussion: The research reveals that while venture capital, crowdfunding, and debt financing each play significant roles in fostering innovation, their effectiveness is heavily influenced by external factors such as supportive government regulations and dynamic market conditions. The study highlights the importance of financial literacy and access to investor networks as critical barriers and opportunities for entrepreneurs. Implications: This study provides valuable insights for policymakers, investors, and entrepreneurs, emphasizing the need for tailored financial strategies and supportive regulatory environments to enhance innovation. The findings suggest that fostering a more inclusive and sustainable entrepreneurial ecosystem requires collaboration among all stakeholders, with a particular focus on leveraging technology to democratize access to capital.